Development of a genomic DNA reference material panel for thalassemia genetic testing. (16th April 2020) - Yin, Zhenzhen; Qu, Shoufang; Huang, Chuanfeng; Chen, Fang; Li, Jianbiao; Chen, Shiping; Ye, Jingyu; Yang, Ying; Zheng, Yu; Zhang, Xi; Yang, Xuexi; Xie, Longxu; et al.
Abstract: Introduction: Thalassemia is one of the most common autosomal recessive inherited diseases worldwide, and it is also highly prevalent and variable in southern China. Various types of genetic testing technologies have been developed for diagnosis and screening of thalassemia. Characterized genomic DNA reference materials (RMs) are necessary for assay development, validation, proficiency testing, and quality assurance. However, there are no publicly available RMs for thalassemia genetic testing as yet. Methods: To address the need for the publicly available DNA RMs for thalassemia genetic testing, the National Institutes for Food and Drug Control and the China National GeneBank established 32 new cell lines with three wild‐type genotypes and 29 distinct genotypes of thalassemia which account for approximately 90% thalassemia carriers in China. The genomic DNA of 32 cell lines was characterized by four clinical genetic testing laboratories using different genetic testing methods and technology platforms. Results: The genotyping results are concordant among four laboratories. In addition, the results of stability test demonstrated that the genotypes of these DNA samples are not influenced by preanalytical conditions such as long‐term exposure to high‐temperature (37°C) environment and repeated freeze‐thawing. Conclusion: We developed the first national panel of 32 genomic DNA RMs which are renewable and publicly available for the quality assurance of various genetic testing methods and will facilitate research and development in thalassemia genetic testing.